“Nascer como uma algaroba e crescer como um juazeiro” - os Xokó da ilha de São Pedro - Souza, Jucimara Araujo Cavalcante (2016)
This research focused on Xokó, a small indigenous community, which are located on the São Pedro’s island, the low part São Francisco river, in the state of Sergipe, northeastern Brazil. The community has undergone a process of territorial recovery at the end of the 1970s, supported by the liberation theology of the Catholic Church. The church that acted different from their ancient missionary practice, now valuing differences. With the recovery of the territory, then the caboclos of Caiçara gradually began to reorganize as a collective indigenous. Thus, through ethnographic incursions in the community, this research reflects on the new forms of social organization that is forged between Xoko from two processes observed: the resumption of ouricuri ritual and the choice of a new chief in ritual context. My hypothesis is that after the reconquest of the territory, these processes contributed to the community to invest increasing efforts in a way of "strengthening the culture “, which involved a deepening in the ritualistic language of toré in its variant , the ouricuri.